The offshore world according to FATCA: new evidence on the foreign wealth of US households - Johannesen, N; Reck, D; Risch, M; Slemrod, J; Guyton, J; Langetieg, P (University of Chicago Press, 2024)
This paper uses account-level information, reported to the US Internal Revenue Service by foreign financial institutions under the Foreign Account Tax Compliance Act (FATCA), to produce new evidence on the foreign financial wealth of US households. We find that US taxpayers hold around $4 trillion in foreign accounts, almost half in jurisdictions usually considered tax havens. Combining the FATCA reports with other administrative tax data and tracing account ownership through partner-ships, we document a steep income gradient in the propensity to hold assets in foreign financial institutions. Specifically, more than 60% of the individuals in the top 0.01% of the income distribution own foreign accounts, the vast majority in tax havens and more than half through a partnership. We discuss the likely implications of these findings for the overall impact of FATCA on tax compliance and government revenue.